Gut microbiota, circulating metabolites, and gallstone disease: a Mendelian randomization study - Hu, Xutao; Binxu, Qiu; Shao, Guang-zhao; Huang, Yu; Qiu, Wei (Frontiers in Microbiology, 2024)
The link between Gut microbiota (GM) and Gallstone disease (GSD) is well established, but it is not clear whether there is a causal relationship between the two associations.We conducted bidirectional Mendelian randomization (MR) analyses, leveraging aggregated data from the Genome-Wide Association Study (GWAS) of GM and Circulating Metabolites. Our primary objective was to investigate the causal interplay between intestinal flora and GSD.Additionally, we performed mediational analyses, two-step MR, and multivariate MR to uncover the potential mediating effect of circulating metabolites in this relationship.Our study has revealed a causal relationship between GSD and six distinct bacterial groups.genetically predicted Class Bacilli (Odds Ratio (OR): 0.901, 95% Confidence Interval (95% CI):